Translating New Testament Proverb-Like Sayings in the Style of Local Proverbs. Issue 3 (December 2015) - Pluger, Chris
This paper identifies a collection of "proverb-like" sayings found in the Greek New Testament and analyzes some of the grammatical and phonological features that characterize the collection. It then exemplifies the translation of several of these sayings into the Nsenga language as Nsenga proverbs, following the literary functional-equivalence (LiFE) approach described by E. R. Wendland. It is hoped that these "LiFE-like" Nsenga translations can serve as models for the translation of biblical proverbs into appropriate local literary forms in languages around the world.